BRONCHIAL ASTHMA: EPIDEMIOLOGY, ETIOLOGY, PATHOGENESIS, DIAGNOSIS, TREATMENT, COMPLICATIONS, ASTHMATIC STATUS AND ITS TREATMENT (International journal of medical sciences, 2026)
This article extensively covers the current relevance of bronchial asthma, epidemiological distribution, etiology, pathogenesis, diagnostics, treatment principles and complications. Bronchial asthma is a chronic inflammatory disease, which is widespread among children and adults, characterized by its multifactorial development mechanisms and bronchial hyperreactivity. The article describes the main provoking and aggravating factors of the disease, IgE-mediated allergic mechanisms, stages of bronchial obstruction development on a scientific basis. It also shows the importance of modern diagnostic methods, complex treatment approaches and disease control in diagnosing bronchial asthma. The clinical course, stages and role of asthmatic status as a life-threatening condition are emphasized.